Leopold Junek - slikar s dvije domovine - Rauter Plančić, Biserka (Array, 2008)
The masterpieces of the French and Croatian collections of Leo Junek (1899 – 1993), which we have injudiciously forgotten, bear witness to the cultural links between Croatian and French modern art. A retrospective exhibition of the works of Leo Junek, better known in France as Lorris Junec, held this spring at the Zagreb gallery Klovićevi dvori, has forever restored him to the corpus of national art and has promoted on the global cultural stage a production that germinated in Zagreb and grew in Paris and stands firmly at the very peak of universal artistic values in the crosswinds of European artistic expression in the twentieth century. A selection of 158 Junek oils, aquarelles, gouaches and sketches, from the earliest in 1922 to the last works from 1993, depicts a painting creativity in continual growth from discernable talent to an independently created colourism and abstraction in which Leo Junek reached the very peak of French and Croatian contemporary painting. This year's meeting with the paintings of Leo Junek were a true cultural and historical privilege for this generation that the Klovićevi dvori gallery presented as a long awaited unveiling of the grand oeuvre of this painter of two homelands.